2006
DOI: 10.1111/j.1365-246x.2006.02929.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation anisotropy and the relative frequency content of split shear waves

Abstract: S U M M A R YThe variation of frequency-dependent seismic wave attenuation with direction (attenuation anisotropy) contains additional information to that contained in velocity anisotropy. In particular, it has the potential to distinguish between different mechanisms that can cause velocity anisotropy. For example, aligned fracturing might be expected to cause measurable velocity and attenuation anisotropy, while preferred crystal orientation leads to significant velocity anisotropy but may cause only small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…The anisotropic attenuation of rocks is found from ultrasonic observation in the laboratory (Tao and King, 1990;Best et al, 2007;Zhubayev et al, 2016) and from a field seismic survey (Carter and Kendall, 2006;Clark et al, 2009;Behura et al, 2012;Shekar and Tsvankin, 2012). Because waves tend to exhibit anisotropic behavior as a result of the natural thin layering of the earth, we would expect the same waves to experience an anisotropic attenuation for the same reason.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropic attenuation of rocks is found from ultrasonic observation in the laboratory (Tao and King, 1990;Best et al, 2007;Zhubayev et al, 2016) and from a field seismic survey (Carter and Kendall, 2006;Clark et al, 2009;Behura et al, 2012;Shekar and Tsvankin, 2012). Because waves tend to exhibit anisotropic behavior as a result of the natural thin layering of the earth, we would expect the same waves to experience an anisotropic attenuation for the same reason.…”
Section: Introductionmentioning
confidence: 99%
“…(32) tested the (36) model on several microseismic datasets of shear-waves splitting to predict attenuation of the split shear-waves. However, (32) observed that sometimes the fast shearwave was more attenuated at higher frequencies than the slow shear-wave.…”
Section: Amplitude Spectral Ratiomentioning
confidence: 86%
“…However, (32) observe that the fast shear-wave can experience larger attenuation than the slow shear-wave, and suggest that the relative peak amplitude of the split shear-waves are depend more on the initial polarization of the incident shear-wave than on the relative levels of frequencydependent attenuation. The LASR for the Normal model can be simplified based on the assumption that the shear-wave onset times will be equal (t X = t Z )…”
Section: Amplitude Spectral Ratiomentioning
confidence: 86%
“…The latter is a statistical quantity that can be evaluated practically from the discrete Fourier spectrum of the seismic data. In the published literature, some works implement the evaluation of the mean frequency using the power spectrum Lee, 1989, 1990;Barnes, 1993;Loughlin and Tacer, 1997;Loughlin and Davidson, 2001;Carter and Kendall, 2006;Wang, 2014), and other works use the amplitude spectrum (Quan and Harris, 1997;Hu et al, 2013). We derive expressions analytically for both statistical cases and prove that the central frequency is close to the mean frequency evaluated from the power spectrum rather than the amplitude spectrum.…”
Section: Introductionmentioning
confidence: 97%